Preparation and characterization of a poly (1, 4-phenylenevinylene) derivative-based hybrid thin film nanocomposites with enhanced performance. (May 2018) - Belhaj, Marwa; Jemmeli, Dhouha; Dridi, Cherif; Ben Salem, Balkiss; Jaballah, Najmeddine; Majdoub, Mustapha; Yatskiv, Roman; Grym, Jan
Abstract: In this study, a poly (1, 4-phenylenevinylene) derivative (PPV-C6 ) was synthesized via Gilch polycondensation, and its electrochemical and optical characteristics were determined by cyclic voltammetry analysis, ultraviolet–visible, and photoluminescence spectroscopy. The polymer exhibited semiconductor behavior with an optical band gap of about 2.02 eV. Thin-film hybrid nanocomposites were prepared based on PPV-C6 with a large range of concentrations of sol–gel synthesized surfactant-free ZnO nanoparticles (n-ZnO). We investigated the photophysical properties of nanocomposites with different weight ratios of n-ZnO. The optical absorption spectra of PPV-C6 : n-ZnO nanocomposites exhibited moderate variation in terms of the optical band gap energy with respect to the pristine polymer. Photoluminescence spectra indicated that the optimum n-ZnO concentration was about 50 wt% to achieve photoluminescence quenching, which corresponded to the most homogeneous surface and efficient charge transfer due to optimal exciton dissociation. We established good correlations between the investigated properties. Highlights: A PPV derivative was synthesized by Gilch polycondensation. Various concentrations ZnO nanoparticles added to PPV to make hybrid nanocomposites. Optical and morphological properties of the polymer and hybrid thin films studied. Relationships determined between nanocomposite compositions and physical properties.